Penyelesaian Tindak Pidana Secara Diversi terhadap Anak di Wilayah Hukum Kepolisian Resort Langkat - Megayani Umry (CERED Indonesia, 2020)
During the last 2 years there has only been 1 (one) case where efforts were made to diversion, namely LP / 497 / IX / 2020 / SU / LKT 24 September 2020 committed theft of oil palm on plantation land in violation of Article 111 Subs Article 107 letter d of Law Number 39 2014 concerning Plantation. The theft was carried out by the perpetrator taking 15 (fifteen) palm fruit bunches weighing approximately 225 Kilograms (Kg) from the area of the reporter's plantation. However, this is an agreement to do diversion. Based on the background description above, it is interesting to conduct research in this thesis with the title: